Adolescent characteristics and incidence of pre‐malignant disease and invasive tumors of the cervix. Issue 7 (July 2020) - Boker, Lital Keinan; Twig, Gilad; Klaitman‐Meir, Vered; Derazne, Estela; Shina, Avi; Levine, Hagai; Kark, Jeremy D
ABSTRACT : Introduction : Pre‐malignant cervical disease and invasive cervical cancer present a significant global health burden with respect to morbidity and mortality, mostly in low‐ and middle‐income countries. Human papillomavirus (HPV) infection typically manifests for the first time in adolescence. We aimed to identify adolescent sociodemographic and anthropometric characteristics associated with subsequent risk for pre‐malignant cervical disease and cervical cancer, in a country that offers free screening and HPV vaccines. Methods : This historical cohort study included 969 123 Israeli women examined and anthropometrically measured at age 17 years between January 1967 and December 2011. Data on pre‐malignant disease and invasive cervical tumors were obtained from the national cancer registry by linkage. We excluded non‐Jewish minorities (a total of 25 472 women) and orthodox/ultraorthodox Jewish women since these populations are not required by law to serve in the military, as well as women with a pre‐examination diagnosis of cancer. Cox proportional hazards regression models were applied per each lesion type, adjusted for origin, measured body mass index, height, education, dwelling type, birth year, and age at examination. Results : In total, 5094 and 859 incident pre‐malignant cervical disease and cervical cancer cases, respectively, were diagnosed during a median follow‐up of 17.6 years. Risk for both lesions was origin‐dependent, with higher incidence in women of North‐African origin (HR (pre‐malignant cervical disease) 1.22, 95% CI 1.04 to 1.42; HR (cervical cancer) 1.87, 95% CI 1.30 to 2.69) compared with European origin. Height, lower education, and later birth year were associated with higher pre‐malignant cervical disease and cervical cancer risk also. Adolescent overweight (HR 0.81, 95% CI 0.74 to 0.90) and obesity (HR 0.56, 95% CI 0.43 to 0.71) status were associated with reduced pre‐malignant cervical disease but not cervical cancer incidence, as did urban (vs rural) residence. Discussion : Ethnic background, tall stature, and education were associated with pre‐malignant cervical disease and cervical cancer incidence, while adolescent overweight and obesity were inversely associated with only pre‐malignant cervical disease. Despite free screening and HPV vaccines, these findings suggest that there is still a need for appropriate safe sex and screening education in adolescence.